Comparision of biocompatibility and cytotoxicity of two new root canal sealers - BECEREN, AYFER; ŞENER, GÖKSEL; GENÇOĞLU, NİMET (ELSEVIER GMBH, 2010)
The aim of this study was to investigate the remote organ toxicity and connective tissue reaction of two new root canal sealers (GuttaFlowa(R) and EndoREZ(R)) and to compare them with zinc oxide eugenol sealer using biochemical and histopatho-logical parameters A total of 60 white albino Wistar rats were used in the study 0 1 ml of GuttaFlow(R), EndoREZ(R) or Kerr Pulp Canal Sealer(R) were administered subcutaneously into the mid dorsal thoracic region of rats (15 in each group) Control rats were given saline only Rats were decapitated after 24 h, on day 7 and on day 30 of the experiment and tissue samples from lung, liver, kidney and skin were removed for the determination of malondialdehyde (MDA) and glutathione (GSH) levels In parallel, tissues were also examined histologically Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) levels, and creatinine and blood urea nitrogen (BUN), concentrations (BUN) were measured to assess liver and kidney functions, respectively Tumor necrosis factor (TNF) and lactate dehydrogenase (LDH) were also assayed in serum samples No statistical differences were found among the control and EndoREZ(R), GuttaFlow(R) and Kerr Pulp Canal sealers regarding tissue MDA, GSH levels or serum parameters (p>0 05) at all time points examined Both of the new root canal sealers showed good compatibility and acceptable tissue toxicity (C) 2009 Elsevier GmbH All rights reserved
Keywords: Biocompatibility; Cytotoxicity; EndoREZ; GuttaFlow; Kerr pulp canal sealer; Root canal; Rats; ZINC-OXIDE; COMPONENTS